Six years’ experience and trends of serum 25-hydroxy vitamin D concentration and the effect of vitamin D3 consumption on these trends - Horváth, László; Mirani, Sara; Girgis, Michael Magdy Fahmy; Rácz, Szilvia; Bácskay, Ildikó; Bhattoa, Harjit Pal; Tóth, Béla E. (Frontiers in Pharmacology, 2023)
Introduction Vitamin D (vitD) deficiency may have importance in some diseases, but there is a lack of data in our country to clarify the current situation. Our aim was to examine the basic characteristics of patients’ vitD status, ratio of vitD deficiency and its relation to certain diseases, assess seasonality and trends and reveal the indirect impact of the COVID-19 pandemic on vitD3 supplementation at patient population level. Methods Anonymized data of 25(OH)D test results were obtained from the clinical data registry of a tertiary teaching hospital covering the period between 1 January 2015 and 30 June 2021.VitD consumption (pharmacy sale) was retrieved from the database of National Health Insurance Fund of Hungary in order to calculate DDD/1000 inhabitants/day. Descriptive statistics and odds ratio with their 95% confidence intervals were calculated. Two-sample T test, F test were used to analyse our patients’ data. Significant differences were considered if p<0.05. Results Altogether 45567 samples were investigated, mean age was 49±19.1 years, 68.4% were females. Overall, 20% of all patients had hypovitaminosis D and just over 7% of patients had vitD deficiency. Males had higher odds for hypovitaminosis or vitD deficiency (65.4±28.2nmol/L vs. 68.4±28.4nmol/L; p<0.0001). Mean 25(OH)D concentration has changed during the year, reaching a peak in September and a minimum in February. Patients with diseases of the circulatory system, genitourinary system, certain conditions originating in the perinatal period and ‘sine morbo’ (i.e. without a disease; such as aged over 45 years and female teenagers) had statistically higher odds for lower 25(OH)D concentration (p<0.00001). VitD consumption showed seasonality, being higher in the autumn and winter. A slight increase started in the season of 2017/18 and two huge peaks detected at the beginning of 2020 and 2021 in association with the COVID-19 waves. Conclusion Our data is the first to describe data concerning vitD in our region. It reinforces the notion of vitD3 supplementation for some risk groups and, also in healthy individuals. To prevent the winter decline, VitD3 supplementation should be started in September. This and the results during the COVID-19 pandemic highlight the importance of health education encouraging vitamin D3 supplementation.